1987
DOI: 10.1029/wr023i012p02175
|View full text |Cite
|
Sign up to set email alerts
|

Soil heat and water flow with a partial surface mulch

Abstract: A computer model using the alternating direction implicit (ADI) finite difference method to study two‐dimensional coupled soil heat and water flow with a partial surface mulch cover is developed. A new, simplified computational procedure, which has only tridiagonal matrix problems, for the ADI method is introduced. The model uses a soil surface energy balance equation to determine soil surface boundary conditions for both heat and water flow. The inputs required for the computer simulations are weather data, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
225
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(236 citation statements)
references
References 25 publications
8
225
0
3
Order By: Relevance
“…The water flow and heat transport equations are solved in a fully coupled way. The equation of Chung and Horton (1987) was used to describe the thermal conductivity k (W/m/K) as a function of the volumetric water content:…”
Section: Numerical Modeling 231 Governing Flow and Transport Equatmentioning
confidence: 99%
See 1 more Smart Citation
“…The water flow and heat transport equations are solved in a fully coupled way. The equation of Chung and Horton (1987) was used to describe the thermal conductivity k (W/m/K) as a function of the volumetric water content:…”
Section: Numerical Modeling 231 Governing Flow and Transport Equatmentioning
confidence: 99%
“…Parameters of the empirical function that describes the thermal conductivity as a function of the volumetric water content were calculated using the Chung and Horton (1987) equation based on the two dominant grain sizes of the soils. All thermal conductivity parameters were fixed during the calibration.…”
Section: Model Calibrationmentioning
confidence: 99%
“…have also shown that crop residue that only partially covers soil surface has less effect on E s because of greater surface temperature and larger drying gradients between bare soil and soil under residue covered areas (Willis, 1962;Chung and Horton, 1987;Steiner, 1989;Klocke et al, 2009).…”
mentioning
confidence: 99%
“…The presence of a soil temperature gradient affects not only the transfer of soil water by affecting the physical properties of soil water, but also affects the redistribution of soil water [5,6]. The thermodynamic characteristics of soil are therefore altered, consequently affecting heat flow in soil [7]. This phenomenon shows that a coupling relationship exists between water and heat transfer in soil [8].…”
Section: Introductionmentioning
confidence: 97%